Public Perception of Piriang Dance with Lampu Cogok Performances - Viska Nanggita; Indrayuda Indrayuda (Science and Environmental Journal for Postgraduate, 2021)
This article aims to reveal people's perceptions of the Piriang (Plate) dance with Lampu Cogok (Oil Lamp)in Nagari (Village) Taratak, Lubuak Sikarahsub-district, Solok City. The Piriang dance with Lampu Cogok has a distinctive characteristic: the existence of a lamp placed above the dancer's head, where the local community calls the light by the name Lampu Cogok. Above the dancer's head, a lamp set has led to various comments by the audience about the light. This study used a qualitative approach, while the research object was the Piriang dance with Lampu Cogok,which originated from the Nagari Taratak, Tanah Garam sub-district, Solok City. The subjects of this study were artists and the general public who watched the dance performance Piriang dance with Lampu Cogok. Techniques of data collection were done through observation, interviews, and documentation. The data analysis technique was carried out with procedures, namely data reduction, data display, and data verification. The results found were that the community's perception, the Nagari Taratak, Especially the traditional elders and the elderly, considered the dance to Piriang dance with Lampu Cogok to be a cultural heritage preserved, especially in the village. Taratak because this dance is a cultural icon in the Nagari Taratak. ThePiriang dance with Lampu Cogok is considered exciting and unique by the community through the presentation of the dance using lights. Besides, the level of complexity and skill, and vigilance of this dance attract and amazes the audience. The lamp above the head becomes the center of attention of the audience. Every time there is a performance of this Piriang dance with Lampu Cogok, it creates debate among the audience about the existence of the lamp. The discussion focuses on whether or not the light is dangerous for the dancers.